Reality as Stratification of Surfaces: The Concept of Transit in Perniola’s Philosophy - Enea Bianchi (EJP import test, 2018)
Summary: The aim of this paper is to show in what terms reality can be considered as a stratification of surfaces by developing Mario Perniola’s philosophy of transit. The first part will deal with the etymology of the word transit, in order to explain its meanings and uses. As it will be clarified, the development of the notion of transit goes together with the conception of reality as deep in the sense of full, available, rich, as the realm of “difference” and “enigmas”. The second part will explain the particular conception of temporality implied in the transit. Together with Perniola’s analysis, Nietzschean and Deleuzian reflections about “amor fati” and “eternal return” will be further explored. This concept is crucial to understand not only Perniola’s overall philosophy by clarifying his position against postmodern thinkers; it also provides a theoretical framework from which the task and the challenge of the philosopher in the contemporary world emerge.
Keywords: Amor Fati; Enigma; Eternal Return; surface; Transit